Evaluation of histopathological patterns of testicular biopsies in azoospermic patients: A study of 3 years in Al-Najaf Center - Shaymaa Ahmed Hadi Allebawi; Asaad Abdul Hamza Al-Janabi (Medical Journal of Babylon)
Abstract Background: Testicular biopsy is still considered the main dependable technique required for the assessment of azoospermic patients. Many studies have been done to explore the main changes that occurred in testicular tissue related to the status of azoospermia. Little has been written and published in our country, so this study has been conducted to look for how much the histopathological pattern plays a role in the assessment of azoospermic testicular biopsy. Objectives: To evaluate the most common histopathological patterns of testicular specimens from male patients in whom the chief complaint is azoospermia and to categorize each case according to the Modified Johnson’s scoring system. Materials and Methods: A cross-sectional study, including a review of 180 male patients with a history of infertility with azoospermia or cryptorchidism, aged 18–60 years, submitted for histopathological examination, in Al-Najaf center for histopathology, during a period of 3 years (2020–2022). Results: A total of 180 cases of testicular biopsy from azoospermic patients were evaluated. The most frequent type is germ cell maturation arrest (84 cases) (46.67%) which is further categorized into early and late arrest with a spermatogenesis score 3–7 according to the Modified Johnson’s score. The second most frequent type is germ cell aplasia/sertoli cell-only syndrome (54 cases) (30%) with spermatogenesis scored as 2. Conclusion: This study has recognized four histopathological patterns of testicular biopsies in the case of azoospermia and identified that germ cell maturation arrest was the most frequent pattern in our population.